2000
DOI: 10.1007/s002390010108
|View full text |Cite
|
Sign up to set email alerts
|

Replication Orientation Affects the Rate and Direction of Bacterial Gene Evolution

Abstract: Abstract. In many bacterial genomes, the leading and lagging strands have different skews in base composition; for example, an excess of guanosine compared to cytosine on the leading strand. We find that Chlamydia genes that have switched their orientation relative to the direction of replication, for example by inversion, acquire the skew of their new "host" strand. In contrast to most evolutionary processes, which have unpredictable effects on the sequence of a gene, replication-related skews reflect a direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 19 publications
2
33
0
Order By: Relevance
“…Genes that switch off replicating strands following chromosomal rearrangements evolve faster to adapt to the composition of the new replicating strand. As a result they show lower mean sequence similarity (Tillier & Collins, 2000b). The ratio of synonymous/non-synonymous rates of switched genes is similar to that of the average orthologues, in agreement with a mutational driving force for this process (Rocha & Danchin, 2001).…”
Section: Compositional Strand Biassupporting
confidence: 60%
See 1 more Smart Citation
“…Genes that switch off replicating strands following chromosomal rearrangements evolve faster to adapt to the composition of the new replicating strand. As a result they show lower mean sequence similarity (Tillier & Collins, 2000b). The ratio of synonymous/non-synonymous rates of switched genes is similar to that of the average orthologues, in agreement with a mutational driving force for this process (Rocha & Danchin, 2001).…”
Section: Compositional Strand Biassupporting
confidence: 60%
“…5, compositional strand bias varies significantly from genome to genome. This may be related to the different stability of the genomes, as chromosome shuffling will tend to level off the bias (Achaz et al, 2003;Mackiewicz et al, 2001b;Rocha et al, 1999b;Tillier & Collins, 2000b). The different length of the Okazaki fragments may also contribute to modulating the bias, since a smaller exposure in the ssDNA state would lead to less cytosine deamination (Mrázek & Karlin, 1998).…”
Section: Compositional Strand Biasmentioning
confidence: 99%
“…It has been shown that genes evolve faster after shifting from one replicating strand to the other due to mutational biases (Tillier and Collins 2000b;Rocha and Danchin 2001). We have examined the translocated genes that shifted strand, but no significant difference in DNA distance was found between genes that shifted strand and those that did not shift strand (see Figure S5).…”
Section: Discussionmentioning
confidence: 99%
“…Relationship between the number of killed genes and N for different F values for three sets of genes after 1000 MCS of simulation is also higher. That means that the observed divergence of genes which recently changed their positions on chromosome should be higher, which was actually observed in numerous genomic analyses ( [6] - [8]). In Fig.…”
Section: Resultsmentioning
confidence: 83%